Bicyclol Alleviates Atherosclerosis by Manipulating Gut Microbiota. Issue 9 (27th January 2022) - Li, Xiao‐Lin; Cui, Jin‐Jin; Zheng, Wen‐Sheng; Zhang, Jin‐Lan; Li, Rui; Ma, Xiao‐Lei; Lin, Miao; Guo, Hui‐Hui; Li, Cong; Yu, Xiao‐You; Du, Peng; Zhao, Li‐Min; et al.
Abstract: Atherosclerosis (AS) is associated with high morbidity and mortality, thus imposing a growing burden on modern society. Herb‐derived bicyclol (BIC) is a versatile bioactive compound that can be used to treat AS. However, its efficacy in AS is not yet described. Here, it is shown that BIC normalizes gut microflora dysbiosis induced by a high fat diet in Apoe (−/−) mice. Metagenome‐wide association study analysis verifies that the modulation on carbohydrate‐active enzymes and short‐chain fatty acid generating genes in gut flora is among the mechanisms. The gut healthiness, especially the gut immunity and integrity, is restored by BIC intervention, leading to improved systemic immune cell dynamic and liver functions. Accordingly, the endothelial activation, macrophage infiltration, and cholesterol ester accumulation in the aortic arch are alleviated by BIC to lessen the plaque onset. Moreover, it is proved that the therapeutic effect of BIC on AS is transmissible by fecal microbiota transplantation. The current study, for the first time, demonstrates the antiatherosclerotic effects of BIC and shows that its therapeutic value can at least partially be attributed to its manipulation of gut microbiota. Abstract : Bicyclol (BIC) effectively modulates the composition, function, and production of endogenous metabolites of gut microbiota. The gut health reinstated by BIC benefits systemic immune cell dynamics and liver functions, leading to improved chronic inflammation and hypercholesterolemia. Consequently, endothelial activation, macrophage infiltration, and cholesterol ester accumulation in the aortic arch are attenuated, causing less plaque onset.